Crossing Cultural Borders: The Social Taboos in Uzbek and Russian Communities (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article explores the differences in taboos between Uzbek and Russian cultures. It starts with an introduction to both cultures and then delves into the taboos that are deeply rooted in each culture. The article explains the significance of taboos such as avoiding physical contact with the opposite sex, disrespecting elders, wasting food, discussing personal matters, dress code, disrespecting the state, discussing politics, drinking in public, and personal space.